1997
DOI: 10.1007/bf02305536
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of lipid content and composition with liposarcoma histology and grade

Abstract: Ex vivo 13C-NMR spectroscopy may be used to distinguish lipoma from well-differentiated, dedifferentiated, and pleomorphic liposarcoma based on changes in lipid and phospholipid metabolite profiles and may serve as adjunct to conventional light microscopy for the determination of liposarcoma histologic type and thus grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
11
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
(15 reference statements)
7
11
0
Order By: Relevance
“…Moreover, our results show that EPA, DHA and arachidonic acid (ARA) are responsible for the higher degree of polyunsaturation in the pathological tissue compared with the normal muscular tissue; these long-chain PUFAs derived, through desaturase and elongase enzyme activity, from the linolenic and linoleic acids, which showed no significant difference in both muscular tissues. Therefore, the observed increase of long-chain PUFAs in this study could be related to the degree of neoplastic cell differentiation, which depends on gene expression and the hormonal environment, with the associated phenotypic change in fatty acid synthesis and degradation, as reported by Singer et al (1997). Thus, these histological types of liposarcoma represent a spectrum of adipocyte differentiation that may be quantitatively characterized by their lipid metabolites (Singer et al 1997), which, in our study showed a marked increase of the long-chain fatty acid synthesis in the pathological muscular tissue.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Moreover, our results show that EPA, DHA and arachidonic acid (ARA) are responsible for the higher degree of polyunsaturation in the pathological tissue compared with the normal muscular tissue; these long-chain PUFAs derived, through desaturase and elongase enzyme activity, from the linolenic and linoleic acids, which showed no significant difference in both muscular tissues. Therefore, the observed increase of long-chain PUFAs in this study could be related to the degree of neoplastic cell differentiation, which depends on gene expression and the hormonal environment, with the associated phenotypic change in fatty acid synthesis and degradation, as reported by Singer et al (1997). Thus, these histological types of liposarcoma represent a spectrum of adipocyte differentiation that may be quantitatively characterized by their lipid metabolites (Singer et al 1997), which, in our study showed a marked increase of the long-chain fatty acid synthesis in the pathological muscular tissue.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, the observed increase of long-chain PUFAs in this study could be related to the degree of neoplastic cell differentiation, which depends on gene expression and the hormonal environment, with the associated phenotypic change in fatty acid synthesis and degradation, as reported by Singer et al (1997). Thus, these histological types of liposarcoma represent a spectrum of adipocyte differentiation that may be quantitatively characterized by their lipid metabolites (Singer et al 1997), which, in our study showed a marked increase of the long-chain fatty acid synthesis in the pathological muscular tissue.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…18 Sarcoma is rare cancer in adults (1%) but there are many subtypes of sarcomas each of which are genetically and biologically distinct such as; liposarcoma, the most common type of soft tissue sarcoma, accounting for approximately 20% of the tumors in adults, is characterized by amplifications of CDK4 and MDM2, malignant peripheral nerve sheath tumors (MPNST), highly malignant tumors of the Schwann cell lineage that have loss of Neurofibromatosis 1 (NF1), Ewing sarcoma (ES), a malignancy of the bone and soft tissue, is characterized by translocations of EWS/FLI1. [19][20][21] Since surgery, radiation and chemotherapy have a limited ability to control inoperable or metastatic disease, there is an extreme need to develop novel targeted therapies and strategies.…”
Section: Introductionmentioning
confidence: 99%